Complete Genome Sequence of Klebsiella pneumoniae Myophage May - Nguyen, Katherine T. (Microbiol Resour Announc, 2019)
May is a newly isolated myophage that infects multidrug-resistant strains of Klebsiella pneumoniae, a pathogen that is associated with antibiotic-resistant infections in humans. The genome of May has been shown to be similar to that of phage Vi01.